OPTIMIZING TIKTOK MEDIA IN STUDENTS LEARNING TO READ STORIES IN THE DIGITAL ERA - Aulia Ulfa; Faradillah Azdina Nur; Isra Thariq (LUMBUNG AKSARA, 2026)
The rapid development of digital technology has significantly transformed various aspects of human life, including the field of education. The integration of technology in the learning process has become an important strategy to enhance the quality of education and to promote more innovative and interactive learning environments. One of the digital platforms widely used by younger generations today is social media. Among these platforms, TikTok, a short-form video sharing application, has considerable potential to be utilized as a creative learning medium. This study aims to examine the benefits of using TikTok in the process of teaching and learning hikayat reading among students in the digital era. The study employs a qualitative descriptive method using a literature review approach. The data were collected from various scholarly sources, including books, academic journals, and research articles related to the use of social media in educational contexts. The findings indicate that the use of TikTok as a learning medium can enhance students’ learning interest, facilitate their comprehension of hikayat texts, and support a more interactive learning process through audiovisual content. Therefore, TikTok can be considered an alternative instructional medium that aligns with students’ learning preferences and needs in the digital era.